Gibson Farm Market Wine Tasting Room grand opening is Nov. 7 - Uribes, Tom::::::::: (2013)
The grand opening for the Rue and Gwen Gibson Farm Market Wine Tasting Room at Fresno State is 3-6 p.m. on Thursday, Nov. 7, kicking off weekly wine tastings.